Belonging, Status, or Self-Protection? Examining Justice Motives in a Three-Level Cultural Meta-Analysis of Organizational Justice Effects. (February 2013) - Fischer, Ronald
The current meta-analysis examines cross-national differences in justice-work attitude and behavior associations to identify underlying justice motives, that is, when and why people pay attention to justice. A three-level meta-analysis with 54, 100 participants from 36 countries was conducted. Income inequality and cultural values were used as moderators after statistically controlling for unreliability of measures. Systematic cross-national differences in justice effects were found. Associations of justice with other work variables are stronger if there is greater income inequality, people expect their leaders and institutions to foster commitment and loyalty (institutional collectivism) and individuals identify with their close in-groups (in-group collectivism). This suggests that belongingness (collectivism) and control (income inequality) motives are important. Implications for justice theories and cross-cultural research are discussed.